Amyloid heart disease: a brief review of treatment options. Issue 1046 (28th June 2012) - Dubrey, Simon W
Abstract : Heart involvement by amyloid deposition remains the most challenging of all organ sytems that may become involved, in what is generally a systemic disease. The correct diagnosis of amyloid type is critical to selection of the appropriate and wide range of therapies. The treatment of amyloid heart disease comprises two strategies: conventional management of a restrictive cardiomyopathy, and varied therapies aimed at the underlying amyloidogenic process. In light chain (AL) amyloidosis, many of the most efficacious therapies involve chemotherapeutic agents with their own inherent toxicities to the heart and bone marrow. In the case of the hereditary amyloidosis, major surgery in the form of liver transplantation is usually required. Moreover, consideration should be given to screening of family members for a potentially hereditary disease. Several types of amyloidosis may require one or more, of heart, liver and/or kidney transplantation, sometimes in addition to high-dose chemotherapy. The objective is to provide a schematic overview of available therapies in the management of AL, hereditary, senile systemic, isolated atrial and secondary forms of amyloidosis.